Electrochemical Reactions at the Boundary Areas Between Cold Atmospheric Pressure Plasma, Air, and Water - Jamiah Thomas; Alexander G. Volkov (Plasma, 2024)
A cold atmospheric-pressure He-plasma jet (CAPPJ) interacts with air and water, producing reactive oxygen and nitrogen species (RONS), including biologically active ions, radicals, and molecules such as NOx, H2O2, HNO3, HNO2, and O3. These compounds can activate interfacial redox processes in biological tissues. The CAPPJ can oxidize N2 to HNO3 and water to H2O2 at the interface between plasma and water. It can also induce the oxidation of water-soluble redox compounds in various organisms and in vitro. This includes salicylic acid, hydroquinone, and mixtures of antioxidants such as L (+)-ascorbic acid sodium salt with NADPH. It can react with redox indicators, such as ferroin, in a three-phase system consisting of air, CAPPJ, and water. Without reducing agents in the water, the CAPPJ will oxidize the water and decrease the pH of the solution. When antioxidants such as ascorbate, 1,4-hydroquinone, or NADPH are present in the aqueous phase, the CAPPJ oxidizes these substances first and then oxidizes water to H2O2. The multielectron mechanisms of the redox reactions in the plasma-air/water interfacial area are discussed and analyzed.